Determinants of Islamic Financial Inclusion in East Kalimantan: Evidence from a Mixed Methods Study - Nuzulia Nuzulia; Isna Yuningsih; Muh Shadiqul Fajri (Al-Tijary, 2026)
Islamic financial inclusion remains a challenge in Indonesia, particularly in regions where access, financial literacy, and public confidence in Islamic financial services vary across communities. This study investigates the factors associated with Islamic financial inclusion across the ten regencies and cities of East Kalimantan, Indonesia, with particular attention to Islamic fintech, trust in Islamic financial institutions, Islamic financial literacy, and attitudes toward Islamic financial services. A sequential explanatory mixed-methods design was adopted. The quantitative phase involved 160 productive-age respondents, with the data analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). This analysis was subsequently complemented by qualitative interviews with representatives of Islamic financial institutions and academia. The results indicate that Islamic fintech has significant effects on both attitudes toward Islamic financial services and Islamic financial inclusion. Trust and Islamic financial literacy significantly influence attitudes but do not have significant direct effects on Islamic financial inclusion. The findings further indicate that attitudes play a mediating role in the relationships between Islamic fintech, trust, Islamic financial literacy, and Islamic financial inclusion. Qualitative evidence highlights digital accessibility, service convenience, and institutional credibility as important factors supporting the adoption of Islamic financial services. At the same time, limited understanding of Islamic financial products, unequal access, and insufficient practical financial experience remain important barriers. These findings suggest that expanding Islamic financial inclusion requires an integrated approach that combines digital financial innovation, stronger institutional trust, improved financial literacy, and wider access to Sharia-compliant financial services.